2018
DOI: 10.1002/dev.21800
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent social stress and social context influence the intake of ethanol and sucrose in male rats soon and long after the stress exposures

Abstract: Social instability stress in adolescent rats (SS; postnatal day 30–45, daily 1 hr isolation +new cage partner) alters behavioural responses to psychostimulants, but differences in voluntary consumption of natural and drug rewards are unknown. SS also is associated with an atypical behavioural repertoire, for example reduced social interactions. Here, we investigated whether SS rats differ from control (CTL) rats in ethanol (EtOH) or sucrose intake in experiments involving different social contexts: alone, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 74 publications
2
17
0
Order By: Relevance
“…Previous research in rats found that when both animals, the demonstrator and the observer (combined exposure), were intoxicated, there was an increase in EtOH consumption, suggesting that when both peers of the dyad are intoxicated, this potentiates the risk for increased adolescent EtOH consumption (Eade et al, ). Recently, it was shown that social instability stress (isolated for 1 hour and then placed with a new cage mate daily) during adolescence (PND 30 to 45) increased intake of EtOH, but not sucrose, when male rats were tested during adolescence (Marcolin et al, ), suggesting that changes in social interaction mediate overall changes in EtOH intake in adolescent male rats. However, these results were not supported in the current study, as changes in EtOH intake were only observed in female adolescent rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in rats found that when both animals, the demonstrator and the observer (combined exposure), were intoxicated, there was an increase in EtOH consumption, suggesting that when both peers of the dyad are intoxicated, this potentiates the risk for increased adolescent EtOH consumption (Eade et al, ). Recently, it was shown that social instability stress (isolated for 1 hour and then placed with a new cage mate daily) during adolescence (PND 30 to 45) increased intake of EtOH, but not sucrose, when male rats were tested during adolescence (Marcolin et al, ), suggesting that changes in social interaction mediate overall changes in EtOH intake in adolescent male rats. However, these results were not supported in the current study, as changes in EtOH intake were only observed in female adolescent rats.…”
Section: Discussionmentioning
confidence: 99%
“…Social influences on alcohol drinking have received attention using rodent models (Doremus et al, ; Eade et al, ; Fernández‐Vidal and Molina, ; Gauvin et al, ; Hunt et al, ; Juárez and De Tomasi, ; Marcolin et al, ; Varlinskaya and Spear, ; Varlinskaya et al, ; Varlinskaya et al, ; Varlinskaya et al, ). In animal models of social influence on alcohol drinking, the most commonly studied behaviors include social play, social investigation, and social contact (Maldonado‐Devincci et al, ; Marcolin et al, ; Varlinskaya and Spear, ; Varlinskaya et al, , ). Adolescent animals seek environmental cues paired with social interactions (Calcagnetti and Schechter, ), and male rats are particularly sensitive to these effects (Maldonado‐Devincci et al, ).…”
mentioning
confidence: 99%
“…Previous research conducted in rats found that when both animals, the demonstrator and observer (combined exposure) were intoxicated, there was an increase in alcohol consumption, suggesting that when both peers of the dyad are intoxicated this potentiates the risk for increased adolescent alcohol consumption (Eade, Youngentob and Youngentob, 2016). Recently, it was shown that social instability stress (isolation for one hour then placed with a new cage mate daily) during adolescence (PND 30-45) increased intake of ethanol, but not sucrose, when male rats were tested during adolescence (Marcolin et al , 2019), suggesting that changes in social interaction mediate overall changes in ethanol intake in adolescent males. However, these results were not supported in the current study, as changes in ethanol intake were only observed in female adolescent rats.…”
Section: Discussionmentioning
confidence: 99%
“…Social influences on alcohol drinking have received attention using rodent models (Gauvin et al , 1994; Juárez and De Tomasi, 1999; Hunt, Holloway and Scordalakes, 2001; Varlinskaya, Spear and Spear, 2001; Varlinskaya and Spear, 2002; Fernández-Vidal and Molina, 2004; Doremus et al , 2005; Varlinskaya, Vogt and Spear, 2013; Varlinskaya, Truxell and Spear, 2015; Eade, Youngentob and Youngentob, 2016; Marcolin et al , 2019). In animal models of social influence on alcohol drinking, the most commonly studied behaviors include social investigation, social play, and social contact (Varlinskaya, Spear and Spear, 2001; Varlinskaya and Spear, 2002; Maldonado-Devincci, Badanich and Kirstein, 2010; Varlinskaya, Truxell and Spear, 2015; Marcolin et al , 2019). Adolescent animals seek environmental cues paired with social interactions (Calcagnetti and Schechter, 1992) and males are particularly sensitive to these effects (Maldonado-Devincci, Badanich and Kirstein, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Male rats subjected to social instability in adolescence show reduced social interactions both immediately following the cessation of stress (Hodges et al, ) and in adulthood (Green, Barnes, & McCormick, ). The same manipulation results in increased ethanol intake in adolescent males (Marcolin, Hodges, Baumbach, & McCormick, ), and remodels dendrites in the medial amygdala (Hodges, Louth, Bailey, & McCormick, ).…”
Section: Introductionmentioning
confidence: 99%